The Effect Of Size And Capital Adequacy Ratio (CAR) On Return On Assets (ROA) With Maqasid Shariah Index (MSI) As A Moderating Variable In Islamic Commercial Banks In Indonesia 2020-2024 - Achmad Agus Yasin Fadli; Andry Priharta (UNIVED Press, 2026)
This study examines the influence of firm size and capital adequacy on the profitability of Islamic commercial banks in Indonesia, with the Maqasid Shariah Index (MSI) serving as a moderating variable. Using panel data from leading Islamic banks over a recent multi-year period, the analysis applies the Common Effect Model and moderated regression to assess both direct and interaction effects. The findings reveal that firm size has no significant impact on profitability, while capital adequacy positively contributes to financial performance. The moderating analysis further shows that MSI does not alter the relationship between firm size and profitability; however, it significantly weakens the positive effect of capital adequacy on profitability, reflecting a shift in strategic priorities toward broader Sharia-based objectives. Overall, the study highlights the differing roles of financial and Sharia-compliance factors in shaping the performance of Islamic banks and provides insights for managers and policymakers in balancing profitability with Maqasid-driven responsibilities.